Design of composition for Mg-Y-Zn-Al alloys using the Taguchi design and analysis of experiments. (21st August 2019) - Liu, Zili; Liu, Guodong; Liu, Xiqin; Xie, Huanjian; Liu, Tianbao; Li, Jian
Abstract: Taguchi design was employed herein to design a series of Mg–Y–Zn–Al alloys and to obtain the composition of the alloy with the best mechanical properties. The alloys were prepared according to the 3-level L9 Taguchi orthogonal table. The signal-to-noise ratios and analysis of variance were used to determine the optimal composition. The microstructures of the Mg–Y–Zn–Al alloys were investigated using an optical microscope, an x-ray diffractometer, a scanning electron microscope and energy dispersion spectra. The optimal composition of the Mg–Y–Zn–Al alloys is 1.2 at% Y content, 0.75 Y/Zn mole ratio and 0.9 wt% Al-5Ti-1B content which corresponds to Mg–4.1Y–4.1Zn–0.9(Al-5Ti-1B) (wt%) with the best mechanical properties. The ultimate tensile strength and elongation of Mg–4.1Y–4.1Zn–0.9(Al-5Ti-1B) (wt%) are 195.35 MPa and 9.45, respectively. The Y content had the largest impact on the ultimate tensile strength and the significant factor that influencing elongation is the Al-5Ti-1B content. Alloys were mainly composed of α -Mg, X phase, Mg4 Y2 ZnAl3, TiB2 and Al2 Y. The TiB2 and Al2 Y, which are formed by the addition of Al-5Ti-1B, can act as heterogeneous nucleation to refine α -Mg grains. The excellent properties of the alloy could be attributed to fine-grain strengthening and second phase strengthening caused by a large amount of X phase and Mg4 Y2 ZnAl3 discontinuously distributed at the grain boundaries.